2021
DOI: 10.3390/pharmaceutics13081219
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Hyperthermia Magnetic Technique Indicating the Best Strategy for Internalization of Magnetic Nanoparticles Applied in Glioblastoma Tumor Cells

Abstract: This in vitro study aims to evaluate the magnetic hyperthermia (MHT) technique and the best strategy for internalization of magnetic nanoparticles coated with aminosilane (SPIONAmine) in glioblastoma tumor cells. SPIONAmine of 50 and 100 nm were used for specific absorption rate (SAR) analysis, performing the MHT with intensities of 50, 150, and 300 Gauss and frequencies varying between 305 and 557 kHz. The internalization strategy was performed using 100, 200, and 300 µgFe/mL of SPIONAmine, with or without Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 79 publications
(94 reference statements)
0
9
0
Order By: Relevance
“…The characterization of MFNP dispersed in culture media confirmed a good MFNP colloidal stability over 18 h, retaining the hydrodynamic diameter of 58 nm, an important aspect of the cell labeling process [13,53,54]. The imbalance of forces involved in the interaction of nanoparticles with the medium can lead them to agglomerate [35,55] and thus to their non-internalization and toxicity for hBM-MSC.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The characterization of MFNP dispersed in culture media confirmed a good MFNP colloidal stability over 18 h, retaining the hydrodynamic diameter of 58 nm, an important aspect of the cell labeling process [13,53,54]. The imbalance of forces involved in the interaction of nanoparticles with the medium can lead them to agglomerate [35,55] and thus to their non-internalization and toxicity for hBM-MSC.…”
Section: Discussionmentioning
confidence: 75%
“…There are certain actions that can improve nanoparticle internalization in cells, such as increasing the period of incubation, surface modification, transfection agents (Poly-D-Lysine and protamine sulfate), and application of magnetic field already evaluated in previous studies [33][34][35][36][37]. The magnetic field attracts the nanoparticle, which contributes to cellular internalization throughout the labeling process [38].…”
Section: Introductionmentioning
confidence: 99%
“…However, before evaluating HSPC biodistribution by ICP-MS, the SPION internalization was confirmed by brightfield microscopy image after Prussian blue staining, in which the internalized nanoparticles are highlighted in the blue color, resulting from the formation of the Fe 4 [Fe(CN) 6 ] 3 complex. This method is widely used in a range of cells, from undifferentiated cells, such as stem and progenitor cells [ 38 , 39 ] to tumor cells [ 40 ], and also reported in HSPC [ 37 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticle cellular uptake and the mechanism of cell death due to hyperthermia are of paramount importance in explaining their eventual clinical applications [ 18 , 19 ]. Mamani et al reported an in vitro study that evaluated the magnetic hyperthermia technique for the internalization of amino saline functionalized ferrite nanoparticles to target glioblastoma tumor cells in static and dynamic magnetic fields [ 20 ]. They were able to achieve up to 70% cell death when exposed for 40 min to an AMF (with a frequency of 557 kHz and an intensity of 300 Gauss).…”
Section: Introductionmentioning
confidence: 99%